Estudo do desempenho do aço válvula austenítico WNr. 1.4882 (X50CrMnNiNbN21-9) laminado a quente sob diferentes níveis de deformação e temperatura - Fernandes, Thaís Melo (Universidade Federal de São Carlos, 2025)
The austenitic valve steel WNr. 1.4882 (X50CrMnNiNbN21-9) is highly alloyed with Cr, Mn, Ni with significant additions of Nb, W, C and N, it has a narrow hot rolling range temperature and is susceptible to cracking during the process. Therefore, the present work aims to study the performance of this steel produced by Villares Metals SA (steelmaker of specialty steels and alloys) when it is hot rolled under different degrees of deformation and temperatures. CALPHAD method was used to predict the precipitation temperatures, mass fractions and chemical composition of the possible phases formed during solidification and steel processing. The forming was done using wedges with geometries and effective deformation levels defined by thermomechanical simulation in Deform 3D®. The research material was rolled at temperatures of 1050, 1100, 1150, 1200 and 1230°C (+30°C in the heating furnace) using a pilot-scale rolling mill at the Villares Metals SA R&D Center. After the process, the microstructures were analyzed via optical microscopy and SEM/EDS and hardness tests were performed in regions with different levels of deformation for each temperature. The results showed that the best temperature range for hot forming of steel occurs between 1100 and 1200°C, condition in which the austenitic matrix contains significant precipitation of only Nb,Cr(C,N). Below this temperature range, there is significant formation of M23C6 at the grain boundaries and precipitation of M2N may occur at points with greater temperature loss, which can make the steel more brittle. In the wedge rolled at 1230°C, the heating temperature (1260°C) exceeded the liquidus of the alloy (1242°C in Scheil) locally in the regions with the presence of M23C6 carbides. Therefore, it is concluded that processing conditions close to the range of 1230-1260°C should also be avoided during forming.
Study of performance of austenitic valve steel WNr. 1.4882 (X50CrMnNiNbN21-9) hot rolled under different levels of deformation and temperature
Keywords: Aço válvula; Aço austenítico nitrogenado; WNr. 1.4882; X50CrMnNiNbN21-9; VV50HCN®; Conformação mecânica; Laminação a quente; Austenitic valve steel; Austenitic high nitrogen steel; WNr. 1.4882; X50CrMnNiNbN21-9; Mechanical conformation; Hot rolling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA